Living citizen brief version 2: Addressing the politics of the health human resources crisis in Canada - Moat, KA; Gauvin, François-Pierre; Lavis, JN (My University, 2023)
A plain-language synthesis of what is known based on the best available global and local research evidence about the problem(s) related to addressing the politics of the health human resources crisis in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This is the second version of this living citizen brief, and it was prepared to inform a living citizen panel.
Living citizen brief version 1: Addressing the politics of the health human resources crisis in Canada
Keywords: politics; health; human resources; crisis; Canada